Crime, Punishment, and Mental Illness Law and the Behavioral Sciences in Conflict - Erickson, Patricia; Erickson, Steven (Critical Issues in Crime and Society, 2008)
Hundreds of thousands of the inmates who populate the nation's jails and prison systems today are identified as mentally ill. Many experts point to the deinstitutionalization of mental hospitals in the 1960s, which led to more patients living on their own, as the reason for this high rate of incarceration. But this explanation does not justify why our society has chosen to treat these people with punitive measures. In Crime, Punishment, and Mental Illness, Patricia E. Erickson and Steven K. Erickson explore how societal beliefs about free will and moral responsibility have shaped current policies and they identify the differences among the goals, ethos, and actions of the legal and health care systems. Drawing on high-profile cases, the authors provide a critical analysis of topics, including legal standards for competency, insanity versus mental illness, sex offenders, psychologically disturbed juveniles, the injury and death rates of mentally ill prisoners due to the inappropriate use of force, the high level of suicide, and the release of mentally ill individuals from jails and prisons who have received little or no treatment